Self-esteem levels among students in a mixed ability 10th grade class at Santo Domingo de Guzmán School in Guayaquil. - Tayarani, Zahra (2017)
The title of this project is Self-Esteem Levels among Students in a Mixed Ability 10th grade Class at Santo Domingo de Guzmán School in Guayaquil. The purpose of this project is to recognize the characteristics of the self-esteem levels identified in a mixed ability 10th grade Class at Santo Domingo de Guzmán of Guayaquil. The methodological scheme of this study comprises the use of a qualitative and quantitative approach, exploring qualitative information such as opinions and motivations which highlight the problems or sometimes helps to develop ideas, as well as considering the quantitative data gathered. The process of gathering information for this project was based on observation, interviews and surveys. The participants of this study are the students, mainly, as well as the teachers from the school and the psychologists. One of the most important conclusions of this project is that there are several levels of self-esteem in an EFL classroom and they present specific characteristics: 1) a high level of self-esteem is characterized by students participating during the class, sharing information and being active in all activities; 2) a medium level of self-esteem is recognizable because their degree of participation was average; and, 3) and a low level of self-esteem presents a lack of motivation of students who seem to be frustrated while watching their classmates participating.